PENTINGNYA ETIKA DAN PROFESIONALISME PENDIDIK DALAM PERKEMBANGAN MORAL PESERTA DIDIK - Sari, Nia Yunia (Ngabari: Jurnal Studi Islam dan Sosial, 2018)
Cases of juvenile delinquency, especially students, are caused by low adolescent morale. The declining moral development of students is usually caused by religious and ethical subject matter which is unable to change student ethics for the better. Student morals are not only the responsibility of parents, but also the responsibility of educators.To be able to fulfill their responsibilities as a good educator, the teacher must have good and professional ethics in doing his job as an educator. This papper aims to find out the importance of the ethics and professionalism of educators in the moral development of students. Educators who have bad ethics and unprofessional educators will not be able to transmit moral education to students. Because in ethical education an educator is an example for students to behave well.